Empirical analysis of traditional akara frying process - Aviara, N. A.; Olarinde, M. O.; Nasirudeen, A. R.; Lasisi, D.; Balogun, L. A.; Ogundare, S. O.; Ogunsola, F. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Akara results from frying of fermented batter which after frying gives a dome –like shape, it has a brown crust and burnt material at the edges. Information on the existence of a mechanical device with capability for frying akara and carrying out turning operations appears to be very scarce. An empirical analysis of the traditional akara frying process was carried out in order to solve the above problem. The effect of different batter concentration (11g/ml, 13g/ml and 17g/ml) and spoon diameter-depth ratio (3.4.4.0,4.2) on the physical characteristics, frying time and frying rate of akara was investigated. The physical characteristics which include crust thickness, level of shrinkage, oil consumption, akara weight, density, surface area and extent of burnt material formation. Data obtained were subjected to statistical analysis using Excel and SPSS. The results showed that crust thickness, level of shrinkage, oil consumption, and burnt material increased with increase in concentration, frying time, weight, density and surface area also increased with increase in concentration. The result also indicates that crust thickness, level of shrinkage, oil consumption, weight, density, surface area, burnt material, frying time, decreases with increase in spoon diameter-depth ratio. Statistical analysis of variance (ANOVA) showed that all the processing variation and their interaction had significant effects on the physical characteristics of akara at 1% of significance. The model yielded coefficients that enabled the akara physical characteristics to be predicted with high coefficient of determination.